Quantum measurement as a thermodynamic resource - Campisi, Michele (Il Colle di Galileo, 2019)
The invasiveness of measurements in quantum mechanics is not necessarily a detrimental effect that needs to be avoided. On the contrary, precisely because it is invasive, the measurement process can trigger an exchange in energy between the measuring apparatus and the object measured, and this can be exploited to fuel an engine, e.g., a quantum refrigerator. In other words, the quantum measurement process can be considered as a genuine quantum mechanical thermodynamic resource.